A red herring without mustard [large type] - Bradley, Alan, 1938- (Bradley, Alan, 1938- Flavia de Luce mystery., 2011)
Camped in her horse-drawn caravan at Buckshaw, a young Gypsy woman is charged with the abduction-and then the murder - of a local child, and Flavia must draw upon her encyclopaedic knowledge of poisons - and Gypsy lore - to prevent a grave miscarriage of justice.